Análisis e interpretación a los estados financieros de la compañía de transporte de carga pesada los panchos s.a., de la ciudad de Yantzaza, periodo: 2013-2014 - Ordóñez Ortega, Gloria Dorila (2016)
This research work is done in order to be able to inform the shareholders and directors of the Company Freight Transport Heavy Los Panchos S.A., the current economic and financial situation of the company and its debt; since after applying an interview with the manager it was found that know about the actual results of the management since only made the financial statements and these are not analyzed minutely. For this reason this thesis entitled "ANALYSIS AND INTERPRETATION TO THE FINANCIAL STATEMENTS OF THE CARRIER HEAVY LOAD THE PANCHOS SA, Yantzaza CITY, PERIOD: 2013-2014" was developed taking into account the Accounting Principles generally Accepted to issue a report attached to reality and with well-founded basis on liquidity, profitability and solvency at the time of both vertical and horizontal analysis and financial indicators applied. This process applied to the Financial Statements allowed concluding that the company does not have sufficient liquidity to meet its short-term obligations and most of its assets are committed to third parties. It could also show that by 2014 the utility obtained a very high reduction tube. It is therefore recommended at the end of each financial year the implementation of a strict analysis of the financial information of the company based on the results, they can take timely decisions either preventive or corrective for the benefit of the company.